Case report: Varicella-zoster virus infection triggering progressive encephalomyelitis with rigidity and myoclonus - Yuan, Jing; Wang, Aihua; Hou, Yunfeng; Xu, Xuxu (Frontiers in Neurology, 2022)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare neurological disease with unknown etiology, and most patients with PERM are positive with anti-glycine receptor (GlyR) antibody. Here we report a clinical case of varicella-zoster virus infected patient who developed anti-GlyR antibody-positive PERM. He initially suffered from herper zoster, and gradually developed symptoms of impaired brainstem functions including hoarse voice and dysphagia, accompanied with paroxysmal sympathetic hyperactivity. The patient also suffered from severe spasms, which were easily triggered by external stimulus. Glycine receptor antibodies were then found to be positive in serum and cerebrospinal fluid, the diagnosis of PERM was determined. Methylprednisolone and gamma globulin treatment were given, and spasms were improved after treatment. Unfortunately, the patient's family insisted on automatic discharge and the patient passed away several days later.